Bridgerton: the viscount who loved me - Quinn, Julia (London Piatkus (Hachette India), 2021)
The second book in the beloved and globally bestselling Bridgerton Family, now a series created by Shondaland for Netflix. Welcome to Anthony's story . . ..1814 promises to be another eventful season, but not, This Author believes, for Anthony Bridgerton, London's most elusive bachelor, who has shown no indication that he plans to marry. And in all truth, why should he? When it comes to playing the consummate rake, nobody does it better... Lady Whistledown's Society Papers, April 1814Anthony Bridgerton needs a wife.Having spent his twenties in a rakish pursuit of pleasure (whilst taking care to ensure the financial security of his mother and seven younger siblings and mother) he knows it's high time he settled down and ensured the continuation of the Bridgerton line.Edwina Sheffield is considered the most beautiful debutante of the current season. She is also sweet, innocent and eminently biddable - Anthony is sure she'll make a perfectly acceptable wife and vows to make her his.The only obstacle in his way is Edwina's older sister, Kate. Kate is determined to do all she can to allow her sister the chance to marry for love rather than convenience. And the roguish viscount is beginning to think he may have met his match in Kate's keen wit and sharp tongue. Until, that is, he makes the mistake of kissing her...Find out why readers love Julia Quinn . . .'Light, pacy and full of feisty heroines' Guardian on the Bridgerton series'Julia Quinn's Bridgerton books take all of the classic tropes we know and love . . . and gives them a thoroughly modern twist. I can't focus on anything else' Stylist'Quinn is a master of historical romance' Entertainment Weekly'A smart, funny touch' Time Magazine'Like an episode of Downton Abbey mixed with a great rom-com' iBooks Best Books of March'Powered by a surfeit of dazzling wit and graced with a cast of unforgettable characters' Booklist'A romance readers will not want to put down . . . Hooray Julia!' Romance Reviews Today'Quinn writes delightfully fast-paced, funny, sparkling and bright romance' Romantic Times'The next best thing to Georgette Heyer' Gloss'Julia Quinn is one of the best historical romance novelists of our time' Heroes and Heartbreakers'Quinn excels in writing stories full of joy and delight, where laughter trembles on the edges' Happy Ever After'Full of wit, charm and smouldering attraction . . . an unputdownable story that I think romance fans will treasure' Harlequin Junkie'Quinn is incomparable
Keywords: Fiction- English; Historical Fiction